ENHANCING ENGLISH PRONUNCIATION STRESS PATTERNS THROUGH LYRIC-BASED SONG ON SPOTIFY - Swara, Marrieta Moddies; Adinda, Lutfia; Sudarmaji, Imam (JETAL: Journal of English Teaching & Applied Linguistic, 2025)
This study investigates the use of songs with moving lyrics on the Spotify app as a medium to improve the pronunciation skills of first-grade vocational high school students. This classroom action research was conducted at SMK TI YPML and employed pre-tests, post-tests, observation checklists, and questionnaires to evaluate the effectiveness of the intervention. The results showed the effectiveness of using songs with moving lyrics on the Spotify app to enhance English pronunciation skills, specifically focusing on stress patterns among students, conducted through a single cycle approach. Pre-test results revealed a mean score of 52, with 80% of students below the competency benchmark of 66. Post-test scores improved significantly, with the average rising to 63 and 60% of students meeting the learning objectives. Observational data indicated high levels of attendance, involvement, and enjoyment, while questionnaire responses showed a good understanding of pronunciation concepts, despite some challenges in engagement and specific sound articulation. These findings demonstrate the positive impact of innovative teaching methods on pronunciation skills, particularly in mastering stress patterns, while also highlighting the need for additional support for struggling students.